Poverty : A Philosophical Approach - Dieterlen, Paulette (Brill Book Archive Part 1, ISBN: 9789004472495., 2005)
In Poverty: a philosophical approach , the author studies various philosophical issues concerning poverty in the Program for Education, Health and Food (PROGRESA) that was in effect in Mexico, from 1997 to 2002, and shows how theoretical discussion is necessary to clarify some ideas concerning the application of a social policy. Poverty is one of the main problems concerning economics, political philosophy, and ethics. It is an ethical problem because of its relationship with self-esteem. Since poverty is intimately related to social policies, the philosophy of poverty must consider the distribution criteria used to attend to people in situations of extreme poverty. This would involve attention to their needs, preferences, capabilities and "well-being" rights. The book considers social policies applied to poverty, and their occasional abuse of utilitarian instruments. Many are implemented without considering cultural differences, including varying patterns of conduct in diverse communities. Equality also matters. Since poverty and inequality are not the same, the study of the latter allows us to target groups found in the lowest levels of "the playing field".